#### Answer

-17

#### Work Step by Step

We know that $\sqrt 289=17$, because $17^{2}=289$.
Therefore, $-\sqrt 289=-(17)=-17$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

-17

We know that $\sqrt 289=17$, because $17^{2}=289$.
Therefore, $-\sqrt 289=-(17)=-17$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.